Adsorption of Copper Ions on the Crosslinked Chitosan Resin - Teng, Yanhua; Xue, Changguo; Zhang, Mingxu (Asian Journal of Chemistry, 2012)
Chemically modified chitosan using glutaraldehyde as crosslinking agent has been use for the adsorption of cupper ions in aqueous medium. The adsorption capacity of crosslinked chitosan resin increased with increasing temperature indicating the endothermic nature of adsorption process. The adsorption process is found to follow the pseudo-first-order kinetic model. IR analysis showed that Schiff base reaction was occurred between the carbonyl group of glutaraldehyde and amine group of chitosan.